Biomimetic microneedles: exploring the recent advances on a microfabricated system for precision delivery of drugs, peptides, and proteins - Chukwuebuka Emmanuel Umeyor; Varsha Shelke; Apurva Pol; Prafull Kolekar; Sarika Jadhav; Nikita Tiwari; Ankita Anure; Abhit Nayak; Ghanshamdas Bairagi; Aniket Agale; Vaishnavi Raut; Sumedh Bahadure; et al. (SpringerOpen, 2023)
Abstract Background Despite its popularity, acceptability, and convenience, the oral route is not the classical route for the administration of all critical bioactives including lipophilic drugs, proteins, and peptides. Recent advances in drug delivery have identified the transdermal route as a compelling alternative channel for improved delivery of essential biomolecules due to the illuminating advantages derived from this route. In order to circumvent the poor permeation of the stratum corneum by transdermal patches, microneedles (MNs) technology, which combine the advantages of parenteral delivery using hypodermic needles and transdermal delivery, has been unveiled as a novel biomimetic technology for efficient and effective transport of payloads across the stratum corneum. Main body of abstract The concept of MNs was first documented by Chambers in 1921 when he reported some problems encountered during experimentation using Echinoderm eggs. Since the first patent recorded in 1976, there has been consistent interest and funding in development of MNs for various biomedical applications. MNs have been developed and classified based on their physical attributes and functional profiles into solid, coated, hollow, dissolvable, and swellable or hydrogel-based MNs. These devices are fabricated using advanced techniques like 3D bioprinting, laser methods, photolithography, and molding, and applying materials such as carbohydrates, silica, ceramics, metals, glass and polymers. MNs could be characterized based on their morphological, geometrical, surface, mechanical properties, biocompatibility, and permeability profiles. Evidences have shown that MNs could be commercialized for various clinical adaptations. The numerous biomedical applications of microneedles in drug, peptide, and protein delivery attest to the versatility and dynamic nature of the fabrication techniques, and the pliability of the formulation materials. In spite of the enormous potentials of MNs, extant literature has shown that MNs also have their own share of limitations like every novel technology designed for theranostic purposes. Short conclusion In this review, we have escalated discussions on the progress and advances made in the development and use of MNs by summarizing the benefits, limitations, fabrication techniques, fabrication materials, characterization methods, therapeutic applications, sterilization and stability considerations, safety and toxicological concerns, regulatory guidelines, and tips for successful commercialization of MNs.